Activities of the summer party of the 30th Japanese Antarctic Research Expedition in 1988-1989 - Sadao Takeuchi (National Institute of Polar Research, 1990)
The 30th Japanese Antarctic Research Expedition (JARE) consisted of 54 members, in which twenty-nine of the wintering party at Syowa Station were led by M.EJIRI, eight of the wintering party at Asuka Station by S.MESHIDA and seventeen of the summer party by S.TAKEUCHI. In addition, two Japanese observers, two Chinese scientists and one Norwegian scientist participated. The icebreaker SHIRASE, leaving Tokyo on 14 November 1988 and after calling at Fremantle, Western Australia, arrived at Breidvika on 17 December. With helicopters, unloadings of about 120t of cargo, eight wintering members for Asuka Station and nine members of the summer expedition party for the Sor Rondane Mountains region (geoscience, biology, and glaciology surveys) were completed on 26 December. Then the ship advanced foward Syowa Station and reached it on 29 December. Unloading of about 820t of cargo, and the summer operations including field research works, the relief of observations, several constructions and renewal of the facilities were carried out until 23 February 1989. The multipurpose satellite data receiving system was also completed. On 1 February all the operations and maintenance of Syowa Station were taken over from JARE-29. There happened the accident that three members of the 29th party fell into the crevasse of the Sor Rondane Mountains area on 13 January, and the ship left Syowa Station for the rescue operation. After picking up the 30th summer party at Breidvika, the ship reached again Syowa Station on 19 February. On 4 March the ship left Lutzow-Holm Bay with the 29th wintering party, the 30th summer party, the observers and foreign scientists, and arrived at Sydney, Australia on 21 March. All expedition members returned to Tokyo on 28 March by air.